Chromosomal insertion of foreign (adenovirus type 12, plasmid, or bacteriophage lambda) DNA is associated with enhanced methylation of cellular DNA segments. - Heller, H (1995)
Insertion of foreign DNA into an established mammalian genome can extensively alter the patterns of cellular DNA methylation. Adenovirus type 12 (Ad12)-transformed hamster cells, Ad12-induced hamster tumor cells, or hamster cells carrying integrated DNA of bacteriophage lambda were used as model systems. DNA methylation levels were examined by cleaving cellular DNA with Hpa II, Msp I, or Hha I, followed by Southern blot hybridization with 32P-labeled, randomly selected cellular DNA probes. For several, but not all, cellular DNA segments investigated, extensive increases in DNA methylation were found in comparison with the methylation patterns in BHK21 or primary Syrian hamster cells. In eight different Ad12-induced hamster tumors, moderate increases in DNA methylation were seen. Increased methylation of cellular genes was also documented in two hamster cell lines with integrated Ad12 DNA without the Ad12-transformed phenotype, in one cloned BHK21 cell line with integrated plasmid DNA, and in at least three cloned BHK21 cell lines with integrated lambda DNA. By fluorescent in situ hybridization, the cellular hybridization probes were located to different hamster chromosomes. The endogenous intracisternal A particle genomes showed a striking distribution on many hamster chromosomes, frequently on their short arms. When BHK21 hamster cells were abortively infected with Ad12, increases in cellular DNA methylation were not seen. Thus, Ad12 early gene products were not directly involved in increasing cellular DNA methylation. We attribute the alterations in cellular DNA methylation, at least in part, to the insertion of foreign DNA. Can alterations in the methylation profiles of hamster cellular DNA contribute to the generation of the oncogenic phenotype?